Survival in Patients With Metastatic Prostate Cancer Undergoing Radiotherapy: The Importance of Prostate-Specific Antigen-Based Stratification - Tian, Zijian; Meng, Lingfeng; Wang, Xin; Wang, Xuan; Ma, Tianming; Wang, Miao; Zhong, Qiuzi; Zhang, Yaqun; Liu, Ming (Frontiers in Oncology, 2021)
Objectives: To explore the effectiveness of radiotherapy in mPCa patients with different PSA stratifications based on the cancer database of a large population. Background: Screening criteria for patients with metastatic prostate cancer, who are candidates for radiotherapy, are rarely reported. Patients and Methods: We identified 22,604 patients with metastatic prostate cancer in the Surveillance, Epidemiology, and End Results database and divided them into a radiotherapy group and a control group. Patients with metastatic prostate cancer were divided into subgroups according to their levels of prostate-specific antigen to evaluate the efficacy of radiotherapy. They were also divided into six subgroups according to their prostate-specific antigen levels. We used multivariate Cox analysis to evaluate overall survival and cancer-specific survival. After 1:1 propensity score matching, Kaplan-Meier analysis was used to explore the difference in overall survival and cancer-specific survival in the radiotherapy and control group. Results: In all, 5,505 received radiotherapy, compared to 17,099 in the control group. In the multivariate Cox analysis, radiotherapy improved overall survival (hazard ratio [HR]: 0.730, 95% confidence interval [CI]: 0.636–0.838; P<0.001) and cancer-specific survival (HR: 0.764, 95% CI: 0.647–0.903; P=0.002) in patients with PSA level of 4–10 ng/mL. Similar results were obtained by Kaplan-Meier analysis after 1:1 propensity score matching. In patients with a prostate-specific antigen levels between 4–10 ng/mL, the overall survival (P<0.001) and cancer-specific survival (P<0.05) in the radiotherapy group was significantly better than the control group. Conclusion: The result of this large population-based study shows that rigorous selection of appropriate metastatic prostate cancer patients for radiotherapy can benefit prognosis significantly. This can be the basis for future prospective trials.